A Fully Recombinant Partial Prothrombin Complex Effectively Bypasses fVIII In Vitro and In Vivo - Himmelspach, Michèle; Richter, Günter; Muhr, Evelyn; Varadi, Katalin; Turecek, Peter L.; Dorner, Friedrich; Schwarz, Hans Peter; Schlokat, Uwe (Thrombosis and Haemostasis, 2002)
The development of inhibitory antibodies is a serious complication in hemophilic patients, severely compromising therapeutic success. Bleeding episodes in affected patients are controlled by treatment with a plasma-derived prothrombin complex concentrate (PCC), activated PCC (APCC) or recombinant activated factor VII. We hypothesized that a recombinant two-component agent consisting of recombinant prothrombin (rfII) and activated factor X (rfXa) would have substantial fVIII bypassing activity and could be a safe alternative therapeutic option. To test this hypothesis we assembled an agent in vitro solely consisting of rfII and rfXa at a molar ratio of 37,500:1. These factors are believed to be responsible for the activity of APCC preparations. Recombinant fX, used as the source for fXa generation, and rfII were purified from serum-free and protein-free conditioned media of stably transfected CHO and BHK tissue culture cells, respectively. Activation of rfX to rfXa was accomplished by the plant protease ficin, obviating the need for a protease derived from a human or animal source. We found that in vitro the complex reduced the abnormally prolonged activated partial thromboplastin time (APTT) of a high-titer fVIII inhibitor plasma similar to an APCC preparation. Furthermore, addition of increasing amounts of rfII/rfXa to inhibitor plasma resulted in a linear dose-dependent increase in the rate of thrombin generation. In a rabbit fVIII inhibitor model, treatment with rfII/rfXa statistically significantly reduced the intensity of the abnormal cuticle bleeding. In the Wessler test, rfII/rfXa showed no thrombogenicity. These data show that a well-defined, particularly safe and efficacious agent with fVIII bypassing activity can be generated from recombinant fII and fXa.
Keywords: Recombinant fII; recombinant fXa; fII/fXa complex; fVIII bypassing activity; hemophilic patient with inhibitors; ficin